Sharing economy and publication trends: a systematic literature review - Spalenza, André Sarmento; Rigo, Ariadne Scalfoni (Revista de Administração da UFSM, 2021)
Purpose: Investigate the phenomenon of Sharing Economy (SE) and propose a literature review of the main trends studying SE. Design/methodology/approach: This is a systematic literature review, based on a bibliographic search conducted on the Scopus, Web of Science, Science Direct and Springer databases. We selected 146 papers extracted from raw data, which were then analyzed by content. Findings: In the analyzed papers, we identified six main scientific approaches to SE, namely: business models for generating value and profit; business that migrate from ownership-oriented to access-focused models; sustainable business in a changing society; new forms of work; regulatory aspects; and conceptual framework analyses. Originality: In a diverse field such as SE, with its different scientific approaches, two stand out in particular: the first is “social change,” caused by a change in perspective, where sharing continues to replace ownership; the second refers to the emergence of new business models that focus on building organizational value and monetary profit, and not necessarily on effecting positive change, either socially or environmentally. This paper analyzes the main scientific biases identified regarding SE studies. The findings indicate paths for further researchers interested in this scientific field, based on the state of the art.